2022
DOI: 10.1101/2022.04.14.22273413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaccine effectiveness of CanSino (Adv5-nCoV) COVID-19 vaccine among childcare workers – Mexico, March–December 2021

Abstract: Background: Beginning in March 2021, Mexico vaccinated childcare workers with a single-dose CanSino Biologics (Adv5-nCoV) COVID-19 vaccine. Although CanSino is currently approved for use in 10 Latin American, Asian, and European countries, little information is available about its vaccine effectiveness (VE). Methods: We evaluated CanSino VE within a childcare worker cohort that included 1,408 childcare facilities. Participants were followed during March–December 2021 and tested through SARS-CoV-2 RT-PCR or r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Convidencia™ can produce high levels of anti-RBA, and its efficacy peaks 2 to 4 weeks after vaccination, gradually diminishing afterwards( 91 ). In addition, a study with healthcare workers showed a 48% effectiveness against PCR confirmed illness( 92 ).…”
Section: Introductionmentioning
confidence: 99%
“…Convidencia™ can produce high levels of anti-RBA, and its efficacy peaks 2 to 4 weeks after vaccination, gradually diminishing afterwards( 91 ). In addition, a study with healthcare workers showed a 48% effectiveness against PCR confirmed illness( 92 ).…”
Section: Introductionmentioning
confidence: 99%